Modeling of the deformation behavior of vanadium under quasistatic loading - Bayandin, Yurii Vitalievich; Kostina, Аnastasia Andreevna; Naimark, Oleg Borisovich; Panteleev, Ivan Alexeevich (Computational Continuum Mechanics, 2012)
The aim of this work is to investigate the role of defects in the formation of properties of metals at early stages of deformation under quasistatic loading using acoustic emission techniques and to provide evidence for structural relaxation phenomena in an ensemble of mesoscopic defects. Based on the previously obtained equations of statistical theory of solid with defects, a mathematical model is proposed for describing the behavior of metals under quasistatic loading and creep conditions. Two order parameters (defect density tensor and structure scaling parameter) are introduced to describe defect evolution in the external stress field. The relationship between the acoustic emission (AE) parameters and the collective behavior of the ensemble of mesoscopic defects is determined.
Keywords: quasistatic loading; elastic viscoplastic model; mesoscopic defects